Uji Bioaktivitas Losartan Terhadap Jaringan Fibrosis Hati Tikus Yang di Induksi Karbon Tetraklorida (CCl4) - Achmad, Anisyah (Jurnal Sains dan Teknologi Farmasi, 2012)
Hepatic fibrosis is an inflammation of  liver which involves series of cells and mediators. Hepatic fibrosis can lead to cirrhosis. Hepatic fibrosis increase the risk of clinical complication such as portal hypertension and hepatocyte disfunction. This study aimed at finding amarker for non invasive hepatic fibrosis or an antifibrotic by comparison of the degree of hepatic fibrosis  after administration of CCl4 and losartan. Thirty five ratâs were divided into 7 groups which were K-1, K-2, K-3, K-4, K-5, K-6, K-7 respectively. K-1 was olive oil control group, K-2, K-3 and K-4 were given CCl4 0,2 ml/100g interperitonially third a week, K-5, K-6 and K-7 were given CCl4 and losartan 5 mg/Kg BB per oral per day. CCl4 and losartan were given for 6 weeks and the change in ratâs hepatic histopathology was observed at week 1st, 4th, and 6th. Histopatology of ratâs liver changed from centrotubular necrosis to centrotubular degeneration but did not show hepatic fibrosis.